TÜRKİYE' DE YAYILIŞ GÖSTEREN BAZI CARDUUS L. (ASTERACEAE) TÜRLERİ ÜZERİNDE KARYOLOJİK ARAŞTIRMALAR - GEDİK, OSMAN (Fırat Üniveristesi, 2014)
Bu çalışmada, Carduus L. cinsinin (Asteraceae) Türkiye' de yayılış gösteren 11 türüne ait (17 takson) 28 örnek (C. olympicus Boiss. subsp. hypoleucus (Bornm.) Davis., C. tmoleus Boıss. (2795-2803-2804-2817-2818-2820), C. nutans L. subsp. falcato-incurvus P. H. Davis. (2737-2798), C. onopordioides Fisch. Ex Bieb. subsp. turcicus Davis., C. candicans Waldst. Et Kit. subsp. candicans Waldst. Et Kit., C. candicans Waldst. Et Kit. subsp. globifer Kazmi., C. acanthoides L. subsp. acanthoides L. (2728-2811-2812-2813-2814), C. acanthoides L. subsp. sintenisii Kazmi., C. nervosus C. Koch. (2753-2756), C. rechingeranus Kazmi., C. argentatus L., C. acicularis Bertol., C. pycnocephalus L. subsp. pycnocephalus L., C. pynocephalus L. subsp. albidus Kazmi., C. pycnocephalus L. subsp. arabicus Nyman. (2741-1040), C. pycnocephalus L. subsp. breviphyllarius Davis.) karyolojik olarak incelenmiştir. İncelenen türlerin kromozom çalışmaları için tohumlarından yararlanılmıştır. Bölünür somatik hücrelerde yapılan çalışmalar sonucunda türlerin kromozom sayımları ve karyotip analizleri yapılarak idiyogramları çizilmiştir. Türlerden; C. nutans subsp. falcato-incurvus (2798) 2n=16, C. candicans subsp. globifer ve C. candicans subsp. candicans 2n=18, C.olympicus subsp. hypoleucus, C.tmoleus (2795-2803-2804-2817-2818-2820), C. acanthoides L. subsp. acanthoides L. (2728-2811-2812-2813-2814), C. acanthoides subsp. sintenisii ve C. rechingeranus' un kromozom sayısı 2n=22 C. acicularis, C. argentatus, C. pynocephalus subsp. albidus 2n=28, C. onopordioides subsp. turcicus, C. nutans subsp. falcato-incurvus (2737) un 2n=32, C. pycnocephalus L. subsp. arabicus' un (2741-1040) ve C. pycnocephalus L. subsp. breviphyllarius kromozom sayıları ise 2n=34, C. nervosus (2753-2756) un kromozom sayısı 2n=50 ve C. pycnocephalus subsp. pycnocephalus' un kromozom sayısı 2n=62, olarak bulunmuştur. Kromozomların; median noktalı (M), median bölgeli (m) ve submedian (sm) sentromerli oldukları tespit edilmiştir. İncelenen Carduus türlerinden C. tmoleus (2820), C. nutans L. subsp. falcato-incurvus (2798), C. candicans subsp. candicans, C. candicans subsp. globifer, C. acanthoides subsp. acanthoides (2811-2812), C. acanthoides subsp. sintenisii ve C. pycnocephalus subsp. breviphyllarius da sattellit gözlenmiştir.

In this study, karyologic properties of 11 species (17 taxa) 28 samples of genus Carduus L. (C. olympicus Boıss. subsp. hypoleucus (Bornm.) Davis., C. tmoleus Boıss. (2795-2803-2804-2817-2818-2820), C. nutans L. subsp. falcato-incurvus P. H. Davis. (2737-2798), C. onopordioides Fisch. Ex Bieb. subsp. turcicus Davis., C. candicans Waldst. Et Kit. subsp. candicans Waldst. Et Kit., C. candicans Waldst. Et Kit. subsp. globifer Kazmi., C. acanthoides L. subsp. acanthoides L. (2728-2811-2812-2813-2814), C. acanthoides L. subsp. sintenisii Kazmi., C. nervosus (2753-2756) C. Koch., C. rechingeranus Kazmi., C. argentatus L., C. acicularis Bertol., C. pycnocephalus L. subsp. pycnocephalus L., C. pynocephalus L. subsp. albidus Kazmi., C. pycnocephalus L. subsp. arabicus Nyman. (2741-1040), C. pycnocephalus L. subsp. breviphyllarius Davis.), which are grown in Turkey, were investigated. Seeds of the examined species were used from for chromosome studies. In consequence of the studies performed in divisible somatic cells, chromosome counts and karyotype analyses of species were examined and idyograms were illustrated. It is found that among species chromosome number for C. nutans subsp. falcato-incurvus (2798) 2n=16, C. candicans subsp. globifer and C. candicans subsp. candicans 2n=18, C. olympicus subsp. hypoleucus, C. tmoleus (2795-2803-2804-2817-2818-2820), C. acanthoides L. subsp. acanthoides L. (2728-2811-2812-2813-2814), C. acanthoides subsp. sintenisii and C.rechingeranus 2n=22, C. acicularis, C. argentatus, C. pynocephalus subsp. albidus 2n=28, C. onopordioides subsp. turcicus, C. nutans subsp. falcato-incurvus (2737) 2n=32, C. pycnocephalus L. subsp. arabicus (2741-1040) and C. pycnocephalus L. subsp. breviphyllarius 2n=34, C. nervosus (2753-2756) 2n=50 and C. pycnocephalus subsp. pycnocephalus 2n=62. It is confirmed that the chromosomes are median point (M), median region (m) and submedian (sm) centromeres. The sattellite was observed in C. tmoleus (2820), C. nutans L. subsp. falcato-incurvus (2798), C. candicans subsp. candicans, C. candicans subsp. globifer, C. acanthoides subsp. acanthoides (2811-2812), C. acanthoides subsp. sintenisii and C. pycnocephalus subsp. breviphyllarius of the Carduus species.
Karyological invesgation on some Carduus L. species spreading in Turkey
Keywords: Biyoloji